Early education in a global context - Sutterby, John A., 1966- (Advances in early education and day care ;, 2012)
This volume of Advances in Early Education and Day Care examines early education from perspectives around the globe. The eight chapters come from a variety of locations including China, Israel, Sweden, Italy, Greece, Zambia, The United States and Canada. These chapters discuss professional development in several contexts, childrens understandings and programs for children. This volume should give the reader an idea of the range of work that is being done around the globe. The unique feature of this volume is that it brings together insider perspectives on early education in different contexts. Each author/s has discussed what is going on in their own context. The Reggio Emilia educational program from Northern Italy has over the last 3 decades had a global impact on early education. This volume seeks to add to the knowledge brought from other diverse sources. The target audience for this book are educational researchers and program developers who are seeking information about international programs.